PS-B08-12: THE REGULATORY EFFECTS OF HYPERTENSION-RELATED CIRCULAR RNA GRB10 IN THE KIDNEY. (January 2023) - Maier, Michelle Carla; Woods, Bradley; Prestes, Priscilla; Byars, Sean; Eales, James; Tomaszewski, Maciej; Charchar, Fadi
Abstract : Objective: To examine the effects of experimental reduction in the expression of circGRB10 in human kidney cells and identify its potential regulatory targets in human kidney cells. Design and method: Through use of small interfering RNA (siRNA), we knocked-down circGRB10 in human kidney cells (HEK293) and investigated potential downstream targets using RNA sequencing. Small RNA sequencing and total RNA sequencing were performed to investigate differentially expressed microRNAs (miRNAs) and mRNAs, respectively. Statistical significance was set as FDR < 0.01. Pathway analysis was performed using Kyoto Encyclopedia for Genes and Genomes (KEGG) on the Database Annotation Visualization Integrated Discovery (DAVID). Finally, we investigated enriched gene ontology terms. Results: We identified 1, 483 genes showing differential expression between cells where circGRB10 was knocked down and the control cells. No miRNAs were differentially expressed between circGRB10 cells and the control. The differentially expressed genes mapped onto 66 KEGG pathways including those of relevance to protein and RNA binding. Conclusion: These results indicate that circGRB10 most likely operates as a direct regulator of mRNA expression in the kidney rather than through modulation of microRNAs.